2019
DOI: 10.1111/coa.13478
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium necrophorum, a major provider of sinus thrombosis in acute mastoiditis: A retrospective multicentre paediatric study

Abstract: Objective To evaluate in children the clinical severity and evolution of otogenic lateral sinus thrombosis (OLST) due to Fusobacterium necrophorum compared with other bacterial otogenic thrombosis and propose a specific management flowchart for Fusobacterium OLST. Design A retrospective multicentre cohort study. Settings Four French ENT paediatric departments. Participants A total of 260 under 18 years old admitted for acute mastoiditis were included. Initial imaging was reviewed to focus on complicated mastoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
(57 reference statements)
0
7
1
Order By: Relevance
“…For how long the antibiotic treatment should be continued is still uncertain. In consideration of the more aggressive clinical presentation, a one-month antibiotic course has been suggested for Fusobacterium infections [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For how long the antibiotic treatment should be continued is still uncertain. In consideration of the more aggressive clinical presentation, a one-month antibiotic course has been suggested for Fusobacterium infections [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors proposed that all patients with an otogenic CVST diagnosis should be screened for thrombophilia in order to evaluate the risk of thrombosis recurrence and treatment duration [9,32]. Nonetheless, thrombophilia screening remains a matter of debate as it is expensive and no evidence of robust proof of its relevance exists [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A signi cant association with otogenic CVST (P < .001) was rst observed in a recent retrospective study by Coudert et al When compared to the CVST from other bacteria groups, the same study showed that children in the CVST Fusobacterium group were signi cantly younger (61 months vs 23 months, P < .01) and had a more severe clinical presentation, with a higher CRP and larger subperiosteal abscess'. These patients generally required a combination of medical and surgical treatment and a longer hospital stay [28].…”
Section: Pathogen Referencementioning
confidence: 99%
“…Nonetheless, thrombophilia screening remains a matter of debate as it is expensive and no evidence of robust proof of its relevance exists [28].…”
Section: Pathogen Referencementioning
confidence: 99%